Oppositional Defiant Disorder: Impacts on child development - Carregosa Ribeiro, Karen Monique (2024)
Introduction: Oppositional Defiant Disorder, also known as Oppositional Defiant Disorder (ODD), is a psychiatric condition characterized by defiant behaviors towards authority figures, often present since childhood. Objective: The objective of this study is to analyze the impacts on child development of children affected by ODD. Methodology: An observational approach was used, reviewing 11 scientific documents published between 2020 and 2024, selected from PubMed and SciELO. The documents were analyzed independently by two reviewers. The results were synthesized and organized for a detailed analysis of the impacts of ODD on child development. Results and Discussion: ODD has significant ramifications on child development, affecting academic performance, social relationships and presenting short- and long-term risks. Manifestations such as irritability and defiance of rules can harm school performance and make social interactions difficult, leading to family conflicts and disciplinary punishments. In the long term, ODD is associated with a greater risk of developing other mental disorders and legal problems, affecting professional life. Final Considerations: The study highlights the complexity of ODD and the need for appropriate interventions. Early and personalized management strategies are essential, as is continued research to develop innovative therapies. The engagement of the scientific community and health professionals is crucial to address the challenges associated with ODD and improve the quality of life of affected children.